GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG KETEPATAN PEMBERIAN MAKANAN PENDAMPING ASI (MP ASI) PADA BAYI (6-24 BULAN) DI BKIA RUMAH SAKIT FATIMA PAREPARE - Yenny Djeny, Randa (Jurnal Kesehatan, 2020)
Appropriate complementary feeding of breast milk (MP ASI) is expected to not only meet the nutritional needs of infants, but also stimulate eating skills and stimulate self-confidence in infants. Supplementary feeding must vary from the form of porridge or liquid to the form of thick porridge, fresh fruit juice, pulverized food, soft food and finally solid food.Research Objectives: To determine the level of knowledge of mothers about the accuracy of breastfeeding complementary feeding (MP ASI) to infants (6-24) at BKIA Fatima Parepare Hospital.Quantitative research with descriptive design. The instrument used is using a questionnaire; From 30 mothers in BKIA Fatima Hospital, Parepare City, based on age 20-30 years as many as 22 people (73%), age 31-40 as many as 8 people (27%), based on high school education as many as 10 people (33%), DIII as many as 2 people (7%), S1 as many as 18 people (60%), based on IRT work as many as 12 people (40%), as many as 10 civil servants (33%), Private Employees / Entrepreneurs as many as 8 people (27%), knowledge about mothers about giving the right MP ASI 28 people have good knowledge (93%), knowledge of mothers about the impact of MP ASI 25 people have good knowledge (83%).Mothers can pay more attention to the nutrition of children and babies according to age so that the development and growth of children and babies is optimal.